Analisis Kestabilan Lereng Pada Penambangan Batu Andesit PT. Ansar Terang Crushindo 1, Kecamatan Pangkalan Koto Baru, Sumatera Barat - Novita Tria Putri; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. The existence of weak fields that affect the stability of the slopes in the mining of PT. Ansar Terang Crushindo 1. The stability of the mine slope is the most important factor that must be considered in the continuation of mining activities. Initial slope geometry has a single slope with a height of 25m with a slope of 820. The slope geometry planning will be used by the Morgenstern Price methods. As a result of research, the following conclusions are drawn. The type of potential that occurred at the study site was a wedge failure with a potential of 10,93%. The analysis characterization of rock mass based on the analysis of RQD, RMR rock types on location classified in the class fair rock. Second, the results of the analysis of single slope of actual earned value FK = 1,911 (natural conditions) and FK= 1,001 (saturated condition). Third, to obtain a safe FK that is 1,3, the geometry of the slope is modified the geometry of the slope is modified, namely with a slope height of 25 m and slope 78° in saturated condition then FK 1,477 slope in safe condition.Keywords : slope stability analysis, RQD, RMR, morgenstern price method, wedge failure